Determinants of cervical cancer screening uptake among reproductive-age women in southwest Ethiopia: a case-control study - Yosef, Tewodros; Birhanu, Bitewlgn; Shifera, Nigusie; Bekele, Bayu Begashaw; Asefa, Adane (Frontiers in Oncology, 2024)
BackgroundCervical cancer is a major global health issue, with 604,000 diagnoses and 342,000 deaths in 2020. Despite the importance of early detection, only 5% of eligible women in Ethiopia are screened. Therefore, this study aimed to assess the determinants of cervical cancer screening uptake among reproductive-age women at selected public hospitals in southwest Ethiopia.MethodsA case-control study involving 392 women (98 cases and 294 controls) aged 15-49 was conducted across three hospitals. Cases were women aged 15 to 49 who had cervical cancer screening, while controls were reproductive-age women seeking antenatal care or family planning but not screened. Data were collected via face-to-face interviews with pretested questionnaires and analyzed using SPSS 25. Bivariate analysis identified candidate variables with P-values < 0.25, and a multivariable logistic regression model determined factors with P-values < 0.05 as significant for cervical cancer screening uptake.ResultsDeterminants of cervical cancer screening uptake included high knowledge of screening (AOR=6.23; 95%CI: 1.96, 19.79), a positive attitude toward screening (AOR=6.12; 95%CI: 2.40, 15.58), women aged 30-39 (AOR=3.94; 95%CI: 1.79, 8.63) and 40-49 (AOR=3.54; 95%CI: 1.52, 8.22), and those who reached health facilities within 60 minutes (AOR=2.32; 95%CI: 1.21, 4.45).ConclusionThe study pinpointed age, knowledge, attitude toward cervical cancer screening, and accessibility to health facilities within a 60-minute radius as pivotal factors impacting cervical cancer screening uptake among reproductive-age women. These findings highlight the importance of targeted education, promoting positive attitudes, and enhancing healthcare accessibility to improve screening uptake and reduce the burden of cervical cancer.